ANALYSIS OF DEBT, AMOUNT OUTSTANDING, STOCK PRICE INDEX, AND NOMINAL EXCHANGE RATE STABILITY OF THE FINANCIAL SYSTEM IN INDONESIA - Radiansyah, Bobby; Suhartoko, Y.B. (Journal Economics & Business Atmajaya Indonesia, 2017)
In this research will be discussed on macroeconomic indicators and financial system stability in Indonesia in period 2000Q1 - 2011Q4. For it will be examined whether there is influence of various macroeconomic indicators in the sample period as well as structural changes to financial system stability in Indonesia. This study uses Error Correction Model. Tests conducted in this study is a data stationary test, cointegration test, test methods Error Correction Model, using a stability test of Recursive Residual Cumulative Sum (CUSUM) and CUSUM of Squares Test (CUSUMQ). To explain the phenomenon of structural changes, were estimated using a dummy variable, during the global crisis in 2008-2009. From the results of these estimates produce a significant effect in the long term the macroeconomic variables on financial system stability in Indonesia although there are some macroeconomic variables the number of foreign debt, the money supply, and the stock price index  which does not have a significant impact on the short term.